2023
DOI: 10.3390/nano13050786
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Electron-Assisted Synthesis of Tailored Magnetite (Fe3O4) and Maghemite (γ−Fe2O3) Nanoparticles: Structure and Magnetic Properties

Abstract: Iron oxide nanoparticles with a mean size of approximately 5 nm were synthesized by irradiating micro-emulsions containing iron salts with energetic electrons. The properties of the nanoparticles were investigated using scanning electron microscopy, high-resolution transmission electron microscopy, selective area diffraction and vibrating sample magnetometry. It was found that formation of superparamagnetic nanoparticles begins at a dose of 50 kGy, though these particles show low crystallinity, and a higher po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…The size is smaller than those observed for Fe 3 O 4 nanoparticles also formed under irradiation at 30 kGy in the presence of PA (D~30 nm) [ 51 ] or synthesized through other methods [ 52 ]. Nevertheless, it is close to that observed for nanoparticles synthesized by radiolytic means in the presence of AG ( Figure S4 ), dextran [ 53 ], or Triton-X [ 26 ]. It should be noted that, with the same stabilizer PA, the sizes of nanoparticles are much smaller (5.2 nm) ( Figure 9 ) when synthesized using the radiolytic route than by coprecipitation (11 nm) ( Figure S3 ), despite a much lower concentration of PA was used (3 × 10 −3 instead of 0.5 mol L −1 ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The size is smaller than those observed for Fe 3 O 4 nanoparticles also formed under irradiation at 30 kGy in the presence of PA (D~30 nm) [ 51 ] or synthesized through other methods [ 52 ]. Nevertheless, it is close to that observed for nanoparticles synthesized by radiolytic means in the presence of AG ( Figure S4 ), dextran [ 53 ], or Triton-X [ 26 ]. It should be noted that, with the same stabilizer PA, the sizes of nanoparticles are much smaller (5.2 nm) ( Figure 9 ) when synthesized using the radiolytic route than by coprecipitation (11 nm) ( Figure S3 ), despite a much lower concentration of PA was used (3 × 10 −3 instead of 0.5 mol L −1 ).…”
Section: Resultssupporting
confidence: 84%
“…Recent studies have demonstrated that superparamagnetic iron ferrite Fe 3 O 4 nanoparticles [ 26 , 27 ] and cobalt ferrite CoFe 2 O 4 nanoparticles [ 28 ] can be synthesized using radiolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the high-resolution TEM (HR-TEM) images (Figure 5a), it was observed that the spacing of two adjacent lattice faces in a specific direction was 0.21, 0.25, and 0.3 nm, corresponding to the lattice spacing of (400), (311), and (220) faces of cubic magnetite, respectively. 51 The crystal phase was further confirmed by SAED (Figure 5b) and XRD images (Figure 6a). For magnetic nanoparticles, there were six diffraction peaks located at 30.1, 35.4, 43.1, 53.6, 57.2, and 62.7°, corresponding to (220), (311), (400), (422), (511), and (440) 9 planes of the cubic spinel structure, respectively.…”
Section: Micromorphology Of Magneticmentioning
confidence: 75%
“…Figure a,b shows that the aggregation of CN-NPs was significantly reduced compared with unmodified Fe 3 O 4 nanoparticles. In the high-resolution TEM (HR-TEM) images (Figure a), it was observed that the spacing of two adjacent lattice faces in a specific direction was 0.21, 0.25, and 0.3 nm, corresponding to the lattice spacing of (400), (311), and (220) faces of cubic magnetite, respectively …”
Section: Resultsmentioning
confidence: 99%
“…The primary purpose of this invention is to recover metal values from iron-containing waste materials and convert them to magnetic γ-Fe 2 O 3 nanoparticles having a wide range of applications from catalysis to waste management [ 9 , 10 ]. It is widely used for the production of, e.g., magnetic materials [ [11] , [12] , [13] ], sensing materials [ 14 ], pigments [ 15 ], sorbents [ 16 , 17 ], photocatalysts [ 16 ], storing data [ 18 ], for biomedical applications such as drug delivery [ 19 , 20 ], contrast agents for resonance imaging [ [21] , [22] , [23] ] and hyperthermia treatment [ 18 , 24 ], as well as being key components for adsorption and storage purposes [ 25 , 26 ]. Recently, iron oxides have been used in a huge amount as electrodes for sodium-ion, lithium-ion, and alkaline-ion batteries [ [27] , [28] , [29] , [30] , [31] ].…”
Section: Introductionmentioning
confidence: 99%